2016
DOI: 10.3389/fimmu.2016.00539
|View full text |Cite
|
Sign up to set email alerts
|

Danger Signals and Graft-versus-host Disease: Current Understanding and Future Perspectives

Abstract: Graft-versus-host response after allogeneic hematopoietic stem cell transplantation (allo-HCT) represents one of the most intense inflammatory responses observed in humans. Host conditioning facilitates engraftment of donor cells, but the tissue injury caused from it primes the critical first steps in the development of acute graft-versus-host disease (GVHD). Tissue injuries release pro-inflammatory cytokines (such as TNF-α, IL-1β, and IL-6) through widespread stimulation of pattern recognition receptors (PRRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 185 publications
0
75
0
1
Order By: Relevance
“…Elimination of this species from the mouse flora before allo‐HSCT aggravates GVHD whereas its reintroduction has the opposite effect . Also, under certain conditions, TLR4 activation seems to have a benefic role against the disease . Together, these data show that environmental factors can both positively and negatively influence HSCT outcome.…”
Section: Introductionmentioning
confidence: 87%
“…Elimination of this species from the mouse flora before allo‐HSCT aggravates GVHD whereas its reintroduction has the opposite effect . Also, under certain conditions, TLR4 activation seems to have a benefic role against the disease . Together, these data show that environmental factors can both positively and negatively influence HSCT outcome.…”
Section: Introductionmentioning
confidence: 87%
“…However, the effectiveness of allo‐HCT is limited by acute graft versus host disease (GVHD) which is the principal cause of non‐relapse mortality . Conditioning regimens used in allo‐HCT cause host tissue injuries which release “danger signals” that activate host or donor antigen presenting cells (APCs) which in turn present allo‐antigens via major histocompatibility complex (MHC) class I or class II to donor T cells . In addition, activated APCs produce T‐cell stimulating cytokines which further escalate the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies of antibiotics to decontaminate the GI tract suggested promising results (91,92), but other studies demonstrated no benefit with broad-spectrum antibiotics. By contrast, a recent analysis demonstrated that broad-spectrum antibiotic use, specifically agents with activity against anaerobes such as imipein intestinal epithelial cells (IECs) and regulates epithelial homeostasis and the gut microbiome (69,76). NLRP6 deficiency improved GVHD, but exacerbated experimental inflammatory bowel disease (76,77).…”
Section: Microbiome and Gi Gvhdmentioning
confidence: 99%
“…Receptors with immunoreceptor tyrosine-based inhibitory motifs (ITIMs) or ITIM-like regions in their intracellular domains regulate DAMP-mediated innate inflammatory responses (65)(66)(67)(68) and belong to the family of sialic acid-binding immunoglobulinlike lectins (Siglecs) (68). Siglec-G expression in host APCs plays an important role in protecting against DAMP-mediated GVHD due to tissue damage following conditioning (69,70). Siglec-G interacts with its ligand CD24, a glycosylphosphatidylinositol-anchored glycoprotein expressed by T cells.…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nmentioning
confidence: 99%